2020
DOI: 10.1088/1755-1315/421/8/082017
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of the spring wheat production process depending on the seeding rate in the arid zone of Mongolia

Abstract: The paper presents the experience of assessing the efficiency of the spring wheat production process depending on the seeding rate in the arid zone of Mongolia. The research was conducted in 2017 at the experimental field of PROLOG SYSTEMS LLC (Mongolia). The experiment used different norms of wheat varieties Novosibirskaya 15. Arable chestnut soils for land use in PROLOG SYSTEMS LLC have the light granulometric composition, characterized by a shortage of productive moisture and a low level of potential fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another biochemical indicator of grain crops is the starch content, which characterizes the availability of carbohydrates in commercial products [16]. It was found that the oat grain, which was grown on a natural agricultural background, contained from 42.9 to 47.2% of starch.…”
Section: Resultsmentioning
confidence: 99%
“…Another biochemical indicator of grain crops is the starch content, which characterizes the availability of carbohydrates in commercial products [16]. It was found that the oat grain, which was grown on a natural agricultural background, contained from 42.9 to 47.2% of starch.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have tempted to investigate the perspectives of using no-till technologies and direct seeding practices to moderate the effects of climate-related parameters on yields [16,[57][58][59][60][61]. Dridiger and Gadzhiumarov [62], Pismennaya et al [20], Goryanin and Shcherbinina [63], Litvinova et al [64], and Boktaev et al [65] are among those few scholars who have tested the possibility and effectiveness of applying the direct seeding method in extremely arid zones in Russia's South and the Volga region, as well as in the countries of Central and East Asia. Although Geleta et al [14] acknowledged the seeding rate to be a critical factor in increasing grain yields, the general finding for extreme arid zones is that the decrease in the seeding rate is permissible, while the productivity of winter wheat is mainly determined by the volume of productive moisture in spring [64,[66][67][68].…”
Section: Introductionmentioning
confidence: 99%
“…Dridiger and Gadzhiumarov [62], Pismennaya et al [20], Goryanin and Shcherbinina [63], Litvinova et al [64], and Boktaev et al [65] are among those few scholars who have tested the possibility and effectiveness of applying the direct seeding method in extremely arid zones in Russia's South and the Volga region, as well as in the countries of Central and East Asia. Although Geleta et al [14] acknowledged the seeding rate to be a critical factor in increasing grain yields, the general finding for extreme arid zones is that the decrease in the seeding rate is permissible, while the productivity of winter wheat is mainly determined by the volume of productive moisture in spring [64,[66][67][68]. However, the dependence of yields on such variables as hydrothermal conditions during the peak periods (extreme droughts or extreme moisture), the duration of the interphase periods of plant development, or plant density has remained underexplored.…”
Section: Introductionmentioning
confidence: 99%